ISOLATION, IDENTIFICATION AND PRESERVATION OF PECTINOLYTIC BACTERIA PATHOGENIC TO POTATO - Lebecka, Renata (Plant Breeding and Seed Science, 2017)
Blackleg of potato plants and soft rot of tubers are caused by several species of pectinolytic bacte-ria from genera Pectobacterium and Dickeya. The text describes simple methods of isolating bacteria from symptomatic and symptomless organs of potato plants, their identification using Polymerase Chain Reaction (PCR) and preservation.